Is Small Better? : A Comparison of the Effect of Large and Small Dams on Cropland Productivity in South Africa - Blanc, Elodie; Strobl, Eric (Oxford University Press on behalf of the World Bank, 2016)
We estimate and compare the effects of small and large irrigation dams on cropland productivity in South Africa. To this end, we construct a panel data set of South African river basins. The econometric analysis reveals that although large dams increase cropland productivity downstream, they have a negative effect on cropland within the vicinity. However, their existence can enhance the relatively small positive impact of local small dams. Although a cost-benefit analysis of irrigation benefits shows that small dams may be more viable than large ones, large dams can play a potentially important role within a system of both types of dams.